Experience of deceased donor kidney transplantation in Brest region - Skachykouskaya, Katsiaryna; Shestiuk, Andrej; Panko, Siarhei; Karpitski, Aliaksandr; Zhurbenko, Gennadij (Medical Studies/Studia Medyczne, 2015)
Introduction : Renal transplantation has progressively increased, and it is the best management of end-stage renal disease. Aim of the research: To evaluate the outcome of renal transplantation from deceased donors to adults living in a region with a population of about one and a half million. Material and methods: A retrospective analysis of the outcomes of 126 recipients of allografts in the period 2011–2014 was performed. The mean age of the recipients was 44.5 ±13.4 years; 71 were male and 55 were female. Kaplan-Meier survival curves were used to assess the graft and recipient survival rates. Results: The overall mortality rate in our study was 4.7% (6 patients), and the mortality of patients with a functioning kidney graft was 3.9% (5 patients). All of them died due to multiple organ failure caused by septic complications of different aetiologies. The data of in our study show that 1-year and 3-year cumulative patient survival after transplantation was 96% and 93.5%, respectively, and the survival rate of kidney grafts was 93% and 68%, respectively. Mean time spent on the renal transplant waiting list had been 31.6 ±7.9 years before the start of the Regional Department of Transplantation, and that was 21.4 ±10.3 (1–141) months in 2014. Conclusions: Three-years of transplant activity in the Brest region resulted in a significant increase in the availability of deceased donor transplantations since every third of the patients with chronic renal failure had kidney allograft transplantation. The 3-year patient survival after transplantation was over 90% owing to up-to-date immunosuppressive regimens and management of postoperative complications.